Shariah issues on selected hybrid products practiced by Islamic banks - Mohd Yunus, Saidatolakma; Mahadi, Nur Farhah; Mahmad Robbi, Ahmad Akram; Embong, Rahimah (Human Resource Management Academic Research Society, 2023)
This article examines the Shariah aspects of certain hybrid products practiced by Islamic banks in Malaysia and provides a comprehensive analysis of the Shariah principles governing the implementation of these hybrid contracts. Among the hybrid contracts, bayʽ bithaman ajil (BBA) and tawarruq have raised concerns due to their potential for facilitating interest (ribā) in buying and selling transactions. On the other hand, other hybrid contracts like mushārakah mutanāqiṣah and murābaḥah to the purchase order are deemed less controversial. When applying these contracts, adherence to important Shariah principles is crucial, including the permissibility of individual contracts, independence of contracts, absence of contradictory commitments, and avoidance of any form of ribā. This study has significant implications for Islamic banking and finance institutions, as well as the Muslim community at large, by promoting the development and provision of Sharia-compliant products and enhancing confidence in their dealings with these institutions.